Emergency Preparedness and Disaster Response: There's An App for That. Issue 5 (15th September 2015) - Bachmann, Daniel J.; Jamison, Nathan K.; Martin, Andrew; Delgado, Jose; Kman, Nicholas E.
Abstract: Introduction: Smartphone applications (or apps) are becoming increasingly popular with emergency responders and health care providers, as well as the public as a whole. There are thousands of medical apps available for Smartphones and tablet computers, with more added each day. These include apps to view textbooks, guidelines, medication databases, medical calculators, and radiology images. Hypothesis/Problem: With an ever expanding catalog of apps that relate to disaster medicine, it is hard for both the lay public and responders to know where to turn for effective Smartphone apps. A systematic review of these apps was conducted. Methods: A search of the Apple iTunes store (Version 12; Apple Inc.; Cupertino, California USA) was performed using the following terms obtained from the PubMed Medical Subject Headings Database: Emergency Preparedness, Emergency Responders, Disaster, Disaster Planning, Disaster Medicine, Bioterrorism, Chemical Terrorism, Hazardous Materials (HazMat), and the Federal Emergency Management Agency (FEMA). After excluding any unrelated apps, a working list of apps was formed and categorized based on topics. Apps were grouped based on applicability to responders, the lay public, or regional preparedness, and were then ranked based on iTunes user reviews, value, relevance to audience, and user interface. Results: This search revealed 683 applications and was narrowed to 219 based on relevance to the field. After grouping the apps as described above, and subsequently ranking them, the highest quality apps were determined from each group. The Community Emergency Response Teams and FEMA had the best apps for National Disaster Medical System responders. The Centers for Disease Control and Prevention (CDC) had high-quality apps for emergency responders in a variety of fields. The National Library of Medicine's Wireless Information System for Emergency Responders (WISER) app was an excellent app for HazMat responders. The American Red Cross had the most useful apps for natural disasters. Numerous valuable apps for public use, including alert apps, educational apps, and a well-made regional app, were also identified. Conclusion: Smartphone applications are fast becoming essential to emergency responders and the lay public. Many high-quality apps existing in various price ranges and serving different populations were identified. This field is changing rapidly and it deserves continued analysis as more apps are developed. DJ Bachmann, NK Jamison, A Martin, J Delgado, NE Kman .Emergency preparedness and disaster response: there's an app for that .Prehosp Disaster Med .2015 ;30 (5 ):1 –5 .